Numerical Modeling Approaches of FRCMs/SRG Confined Masonry Columns - Ombres, Luciano; Verre, Salvatore (Frontiers in Built Environment, 2019)
The Fabric Reinforced Cementitious Matrices (FRCMs) and Steel Reinforced Grout (SRG) are a promising strengthening solution for existing masonry since inorganic matrix is considerably compatible with historical substrates. The present paper is focused on a Finite Element (FE) analysis of masonry columns confined with FRCM composites developed by Abaqus-code. The masonry columns were modelled using a macro model approach. The model was performed by using the following functions Concrete Damage Plasticity (CDP) and the Plastic (P) in order to describe the constitutive laws of material for masonry columns and external reinforcement, respectively. Typical failures of FRCM-systems are slippage of the fibers within the embedding matrix, instead for SRG-systems are detachment of the composite strip at the fabric-matrix interface and fiber rupture. In addition, perfect bond was considered for the interaction between the masonry column and in the overlap zone the bond slip law was modelled on the base of the failure mode. Results of an experimental investigation on FRCM and SRG clay brick masonry columns are used to calibrate the numerical model.